2007
DOI: 10.1590/s0102-77862007000100006
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem da maré meteorológica utilizando redes neurais artificiais: uma aplicação para a Baía de Paranaguá-PR, parte 2: dados meteorológicos de reanálise do NCEP/NCAR

Abstract: A variabilidade do nível do mar observado e a maré meteorológica na Baía de Paranaguá-PR foram analisadas, neste trabalho, com os dados maregráficos utilizados na Parte 1 e os dados meteorológicos de reanálise do "National Centers for Environmental Prediction" (NCEP) e do "National Center Atmospheric Research" (NCAR) pontos de grade no oceano, próximos ao local de estudo, referentes ao mesmo período. As componentes de alta freqüência contidas nos dados de reanálise foram retiradas com o filtro passa-baixa de T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
1
5
0
1
Order By: Relevance
“…Estes autores identificaram bandas de frequências energéticas entre 3 e 10 dias associadas às forçantes meteorológicas, assim como, padrões de propagação de distúrbios do nível médio do mar ao longo da costa sul-sudeste. Mais recentemente, Oliveira et. al.…”
Section: Introductionunclassified
“…Estes autores identificaram bandas de frequências energéticas entre 3 e 10 dias associadas às forçantes meteorológicas, assim como, padrões de propagação de distúrbios do nível médio do mar ao longo da costa sul-sudeste. Mais recentemente, Oliveira et. al.…”
Section: Introductionunclassified
“…To compare the predicted and observed data, several statistical parameters were applied. The RMSE (Root Mean Square Error) calculates the absolute measure of the model deviation from data, being one of the most used error parameters to assess tidal model performance [29,30]:…”
Section: Statistical Parametersmentioning
confidence: 99%
“…The low-pass filter was used to obtain MSL in order to suppress the astronomical and inertial tidal components preserving the 'low' frequency signal (periods longer than three days) -a methodology similar to that used by Oliveira et al (2007). Thompson's (1983) low-pass filter allows its optimization by the user, who defines the main parameters of calculation, especially by imposing preselected cut-off frequencies.…”
Section: Numerical Filteringmentioning
confidence: 99%
“…Several Brazilian authors have applied the low-pass filter proposed by Thompson (1983): i) compared data from the Rio de Janeiro State Tide Gauge Network with meteorological data extracted from the global model of NCEP/NCAR; ii) Oliveira et al (2007) studied the effect of storm surges in Paranagua Bay (PR) and their effects on tidal records from Cananeia (SP); iii) compared Lanczos and Thompson filters' performances in the analysis of MSL variability in the coastal region of Cananeia, and iv) Oliveira et al (2009) analyzed the response of the coastal sea level to atmospheric phenomena through the use of wind and atmospheric pressure data based on the NCEP/NCAR model and tide gauge data from Cananeia (SP). The choice of the Thompson low-pass filter in this study is mainly to be explained as due to its better performance than that shown by Lanczos' results (COSTA;BERNARDES, 2010) and to its versatility in allowing the user to determine the frequencies to be attenuated in the filtering process.…”
Section: Introductionmentioning
confidence: 99%